GKN Electronics Sdn. Bhd. "Increase Profits By Reducing The Bottom Line Through Cost Reduction Programme" - OOi, Hooi Pheng (2005)
This case writing is intended to study comprehensively and thus explore the case of GKN Electronics Sdn. Bhd. to bring technical solusions to cost. This study gives many practical ways of reducing costs.